PENINGKATAN KEMAMPUAN PENGUCAPAN BAHASA INGGRIS SISWA MELALUI VIDEO YOUTUBE DI MADRASAH IBTIDAIYAH MA'ARIF DARUSSALAM - Surahman, Dede (Jurnal Pengabdian Kepada Masyarakat Mulia Madani Yogyakarta, 2025)
In the era of 5.0, English pronunciation ability becomes one of the important competencies for MI students after graduating from school. However, not all students can follow English learning easily because they find it difficult to pronounce English vocabulary and sentences correctly. Therefore, this training activity aims to improve the pronunciation of English vocabulary and sentences through YouTube videos. The method used is audio-visual. The training process includes teaching preparation, training implementation, and evaluation. The results of this activity show that all students participated in the training enthusiastically and improved their pronunciation of English vocabulary and sentences better than before it. The average student has corrected pronunciation and intonation. This activity is expected to support students in learning English at school more enthusiastically and inspire teachers to use more varied, innovative, and engaging methods and media.